2008
DOI: 10.1302/0301-620x.90b3.19782
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between obesity and the age at which hip and knee replacement is undertaken

Abstract: We audited the relationship between obesity and the age at which hip and knee replacement was undertaken at our centre. The database was analysed for age, the Oxford hip or knee score and the body mass index (BMI) at the time of surgery. In total, 1369 patients were studied, 1025 treated by hip replacement and 344 by knee replacement. The patients were divided into five groups based on their BMI (normal, overweight, moderately obese, severely obese and morbidly obese). The difference in the mean Oxford score a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(97 citation statements)
references
References 14 publications
6
84
0
4
Order By: Relevance
“…This subgroup is also at risk for severe complications such as infection. This is consistent with Changulani et al [8] who found those in the morbidly obese range were almost 10 years younger on average than those in the normal weight category, and those with higher body weights were more likely to experience adverse surgical outcomes than those who were not. This also accords with Tai et al [9] and with Guetner et al [10].…”
Section: Discussionsupporting
confidence: 91%
“…This subgroup is also at risk for severe complications such as infection. This is consistent with Changulani et al [8] who found those in the morbidly obese range were almost 10 years younger on average than those in the normal weight category, and those with higher body weights were more likely to experience adverse surgical outcomes than those who were not. This also accords with Tai et al [9] and with Guetner et al [10].…”
Section: Discussionsupporting
confidence: 91%
“…Obese patients appear to undergo TKAs at younger ages, and those reconstructions may be associated with lower implant survivorship [6,36]. In addition, arthroplasties may be more technically demanding in these patients as a result of difficulty in identifying the anatomic landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with an increase in medical comorbidities including hypertension, coronary artery disease, diabetes, and degenerative joint disease [7,32]. These patients potentially may be at increased risk for having osteoarthritis develop, and may need TKA at an earlier age [6,26]. However, surgical interventions in these patients may be associated with more technically demanding procedures and higher complication rates [3].…”
Section: Introductionmentioning
confidence: 99%
“…По статистике па-циенты с ИМТ > 35 кг/м 2 предпочитают пройти операцию по поводу ОА в более раннем возрасте [22]. Причины этого явления многофакторны, но вероятно, тучные пациенты при остеоатрите ищут радикальный и более быстрый вариант ре-шения проблемы, чем пациенты с нормальным ИМТ.…”
Section: особенности этиопатогенеза развития остеоартрита при ожиренииunclassified